Biofunctional properties and plant physiology of Kaempferia spp.: Status and trends. (May 2022) - Hashiguchi, Akiko; San Thawtar, May; Duangsodsri, Teerarat; Kusano, Miyako; Watanabe, Kazuo N.
Graphical abstract: Highlights: The health benefits of Kaempferia spp. include antibacterial, anticancer, antidiabetic, cardiovascular protective, immunoregulatory, neuroprotective, and skin-whitening effects. Bioactive polymethoxyflavones and ethyl p-methoxycinnamate play a role in biological activity of Kaempferia spp.. Kaempferia spp. can target and regulate multiple pathways related to the enhancement of health and vitality. Studies related to value-added production of K. parviflora, such genotype × environment × management practices are limited. Abstract: Kaempferia spp. have traditionally played a role in treating various ailments and are attracting increasing economic and scientific interest. This review evaluates the traditional use, phytochemical compounds, and biological properties of Kaempferia parviflora, Kaempferia galanga, Kaempferia rotunda, Kaempferia pulchra, and Kaempferia angustifolia . The health benefits associated with consuming Kaempferia spp. and their active components, namely flavonoids and other volatile compounds, include antibacterial, anticancer, antidiabetic, cardiovascular protective, immunoregulatory, neuroprotective, and skin-whitening effects, suggesting the use of Kaempferia spp. as a potential health aid for the aging population. As agricultural production is important to ensure consistent quality of Kaempferia produce, resource management techniques related to species identification, cultivation, storage, and processing were also highlighted. It was suggested that the value-added concept in agricultural production may be limited. Investigations into plant biology and physiology are required to provide a solid theoretical basis for the sustainable production of Kaempferia .